Spreminjanje rabe tal v vzhodnih Ljutomersko-Ormoških goricah v obdobju 2000-2015 v povezavi z izbranimi fizično geografskimi značilnostmi - Žiberna, Igor (Revija za geografijo, 2015)
Eastern Ljutomersko-Ormoške gorice are among the most vital vineyard areas of Northeastern Slovenia. Nevertheless, the region has not been spared from the processes of deagrarization and subsequent land use changes which are going in the direction of the abandonment of cultivated areas, greening, overgrowth and afforestation. The article analyses land use changes in the area of Eastern Ljutomersko-Ormoške gorice between 2000 and 2015 in relation to selected physiographic features. Main focus was on cultivated areas, particularly vineyard areas. The directions of land use changes for the studied period are also analysed.
Keywords: Ljutomersko-Ormoške gorice; raba tal; severovzhodna Slovenija; spremembe; vinogradništvo